Ion-Pair Extraction Spectrophotometric Determination of Trace Amounts of Imipramine - Sheibani, M.; Afshar, Z.G. (Asian Journal of Chemistry, 2013)
A simple, sensitive and selective extraction-spectrophotometric method for the determination of trace amounts of imipramine is reported. The imipramine-orange II ion-pair in acidic media is quantitatively extracted into chloroform and its absorbance is measured at 487 nm at room temperature. The effect of different variables such as solvent, volume of extracting solvent, volume of anionic reagent, pH, ionic strength (NaCl 0.1 M) and shaking time is investigated and optimum conditions for quantitative extraction of imipramine is obtained. Linear calibration graph over the imipramine concentration range of 0.03-7.00 μg mL–1 and regression coefficient of 0.9999 is obtained. The relative standard deviation of 10 replicate determination of 2 μg mL–1 of imipramine is 1.945 %. Limit of detection of the method is 0.022 μg mL–1. The method is used for determination of imipramine in 10 mg, 25 mg, 50 mg tablets.